Gamification contributions in ELT learning environments - ESL teachers’ attitudes and perceptions on express digibooks platform - Baltatzi, Pelagia (Language Center, Cyprus University of Technology, 2020)
Gamification in education plays an important role as it constitutes a way of combining fun with learning. This aspect also applies in Second Language (L2) learning. In the past according to previous research in various contexts of the field, Gamification in L2 learning had been mostly related with students' performance in the target language. There was limited research on teachers’ perceptions and attitudes regarding gamification contributions and potentials. This study aimed at reporting and examining L2 teachers’ perceptions and attitudes toward a specific gamification tool, called Express DigiBooks, used in an L2 learning environment located in Greece. This particular aim was reached through a quantitative research design. Thus, it used an online questionnaire as a data collection tool and SPSS as a tool for analyzing this data. The research sample consisted of 75 L2 teachers who responded to particular close-ended questions to the online questionnaire. The study identified all the gamification elements that are considered by L2 teachers as the possible contributors of students’ positive attitudes and motivation, active participation, authentic language use, personalised learning and collaboration during L2 learning. The results of the research, reflecting teachers’ perceptions on the gamification elements which they enjoy using in a particular L2 context, can be linked with other similar results in the field in which L2 teachers had generally positive attitudes toward gamification application in an L2 learning environment.
Keywords: L2 learning; Gamification, teachers’ perceptions and attitudes; Motivation; Active participation; Authentic language use; Personalised learning; Collaboration